THE DEVELOPMENT OF METHOD FOR ACTIVATING PHARMACEUTICAL SUBSTANCES WITH SUBSEQUENT IN SITU STUDY OF MODIFIED POWDER PROPERTIES - USPENSKAYA, ELENA; KUZMINA, EKATERINA S.; QUYNH, HOANG T. N.; TIMOFEEV, ALEKSEY A.; MAXIMOVA, TATIANA V. (International Journal of Applied Pharmaceutics, 2024)
Objective: The aim of this work is to develop a method of activation of pharmaceutical substances by means of a mechanical load on the powder of the substance with the subsequent evaluation on site of the modified preparation. A complex of analytical methods and biotesting were used to characterize the solid-state phase transformation product. Methods: The object of study was powder of the antiepileptic substance Lacosamide (Lcs); Mechanical Activation (MA) of Active Pharmaceutical Ingredient (API) was carried out using the Stegler LM-250 rotary knife mill; Fourier-Transform Infra-Red (FT-IR) spectroscopy in the range of 4000-400 cm-1 was used to analyses the band shift in the spectrum; Dynamic Laser Scattering (DLS) has been used to detect groups of particles ranging in size from 0 to 1000 nm; an innovative method of Two-Dimensional Diffuse Light Scattering (2D-DLS) was used to detect differences in the speckle structure of powder samples before and after modification; Scanning Electron Microscopy (SEM) was used to evaluate particle morphology; X-Ray Fluorescence analysis (XRF) was used to determine the elemental composition of the samples; polarimetry was used to determine the optical activity and Spirotox biotesting has been used to evaluate the biological activity. Results: SEM images of the sample after activation represent a glassy, structurally amorphous state in contrast to the native state. Chemometric processing of FT-IR spectra allowed us to identify the regions of the samples at different activation times on the 2D-diagram of Principal Components Analysis (PCA). According to the XRF data, the elements Fe, Cu, and Zn are predominant in the Lcs-activated sample. The 2D-DLS method revealed differences in speckle structure between samples before and after mechanical activation. The same optical activity of the solutions of the studied samples with preservation of the chiral center was revealed. The Spirotox method showed a 1.6-fold (P≤0.05) increase in biological activity of the activated Lcs sample based on the calculated values of activation energy (bsEa) of the process of cellular transitions to the immobilized state. Conclusion: The developed method of activation of pharmaceutical substances includes a full cycle of 90 min mechanical load chemistry duration with the description of technical equipment and conditions. The results of this study can be used in the pharmaceutical industry to produce preparations with improved physical-chemical and biopharmaceutical properties.